THE EVOLVING DISCOURSE OF FILM REVIEWS: A COMPARATIVE STUDY OF PROFESSIONAL AND AMATEUR APPROACHES - Yesypenko, Nadia; Soloviova, Olga; Hnatkovska, Olena (My University, 2024)
This study illustrates how communicative strategies in amateur and professional film reviews shape readers’ perceptions and preferences, contributing to the evolving landscape of film criticism in the digital age. Its purpose is to examine the communicative purposes of authors of the aforementioned types of reviews and their intended impact on readers through strategic and tactical language use. It employs a communicative and pragmatic approach to explore why readers increasingly prefer amateur film reviews over professional ones, focusing on the strategic and tactical differences between the two. Data for the research have been drawn from professional film reviews in The Guardian and amateur film reviews on Rotten Tomatoes, representing heterogeneous genres and scores. The analysis highlights significant differences in the use of communicative strategies and tactics in professional and amateur film reviews. Firstly, two-thirds of all identified strategies have been found in the amateur reviews. Secondly, both review types are characterised by the dominance of the informative communicative strategy, which underscores its alignment with the primary purpose of film reviews: to provide concise, objective information. Professional film reviews, however, tend to avoid author self-presentation tactics. Thirdly, the emotional and motivational communicative strategy, whose aim is to appeal to audience values and experiences, is more common in amateur reviews, thus fostering personal engagement and challenging conventional perspectives. Professional reviews, on the other hand, prioritize objective analysis of technical and industry-specific aspects, distinguishing them from the emotionally driven focus of amateur critiques. Therefore, amateur reviews often feel more relatable and personal, which can enhance their credibility. In contrast, professional reviews tend to adopt a detached and structured tone, prioritizing the delivery of facts and critical assessment. While this approach supports objectivity, it might not resonate as strongly with certain audiences. These findings underline the evolving nature of film criticism and its dual role in catering to both subjective and objective reader expectations.
Keywords: amateur film review, communicative strategy, communicative tactics, professional film review, speech move